The Impact of Antibiotics on the Gut-Brain Axis - Odeh, Sufian (My University, 2013)
The gut and brain are involved in a bi-directional communication system, referred to as the gut-brain axis. While it has been established that antimicrobials induce dysbiosis in the gut, which further disrupts immune and metabolic homeostasis, research on brain and behaviour development is becoming a topic of interest. We propose that alterations via antibiotics at the level of the gut microbiota impacts the gut-brain axis. The primary interest of this thesis is to understand the effects that antibiotics have on brain and behaviour development in conjunction with changes in the immune system and metabolism using the antibiotic mouse model. Mice treated with antibiotics revealed behavioural differences in the open field apparatus and three-chamber social behaviour apparatus, but not in the elevated plus maze and auditory fear conditionings enclosures. Evaluation of intestinal permeability revealed that female Balb/C mice administered a combination of bacitracin, neomycin and primaricin and another group administered a combination of ampicillin, neomycin and primaricin showed reduced intestinal permeability. Furthermore, the immune system condition was evaluated using flow cytometric analysis of spleens, which revealed no effect of treatment on immune cell profiles in CD1 mice treated with ampicillin. Evaluation of serum cytokine levels showed minimal differences in Balb/C and C57Bl/6 mice treated with antibiotics. Body weight and water and food consumption were evaluated in mice administered antibiotics. Weight loss differences were observed in two groups of female Balb/C mice, with the first group administered bacitracin, neomycin and primaricin and the second group administered ampicillin , neomycin and primaricin. Antibiotic treatment dependent differences in water and food consumption were observed. Serum insulin and leptin level investigation revealed that female Balb/C mice administered ampicillin, neomycin and primaricin had reduced serum insulin levels compared to strain matched controls. These findings indicate that antibiotic treatment impact metabolic function. This pilot study using antibiotic treated mouse models provides insight on the microbiota’s effects on the gut-brain axis, which can help to potentially identify methods of preventing gut microbiota mediated pathology in humans.
Keywords: Gut-Brain Axis; Antibiotics; Gut Microbiota; Intestinal Barrier Permeability; Central Nervous System; Behaviour; Behavioral Neurobiology; Behavior and Behavior Mechanisms; Biology; Developmental Biology; Molecular and Cellular Neuroscience; Other Neuroscience and Neurobiology; Behavioral Neurobiology